Captive-raised western ringtail possums (Pseudocheirus occidentalis) with a bold personality have higher survival rates when released into the wild - Sara Corsetti; Brian Chambers; Dominique Blache; Roberta Bencini (Scientific Reports)
Abstract We tested if the personality of captive-raised western ringtail possums (Pseudocheirus occidentalis), and the impact of other variables would influence their survival after release using radiotelemetry. We hypothesised a greater survival for individuals: (i) bold; (ii) habituated in advance to food collected from the release area; (iii) juveniles instead of adults, because more easily tolerated by wild individuals, and (iv) released in new dreys (nests) as they would not have the strong odour of old dreys and would be less attractive to foxes. After 3 months of radio tracking, out of 143 possums released, 79 died: 51 (64.6%) were preyed upon by European red foxes (Vulpes vulpes). Bold or female individuals had higher survival rates than shy or male individuals (survival rate bold: 53%, shy: 41%, p = 0.046, hazard ratio = 0.352, 95% CI HR [0.126, 0.979]; survival rate females: 44%, males: 35%, p = 0.007, hazard ratio = 2.811, 95% CI HR [1.322, 5.976]). Shooting was a more effective fox control strategy to improve survival compared to baiting (p = 0.019, hazard ratio = 0.167, 95% CI HR [0.038, 0.742]). Our results demonstrate that the control of introduced predators is critical for the success of reintroductions of this critically endangered species.